About eco-feminism ( as a part of environmental ethics ) - Ćorić, Dragana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Women and nature are connected in many different ways : because of their biological status , reproductive  role, discrimination by the " strong ". The representatives of these thinking  find that changing positions and behaviors , ie . leaving the patriarchal approach to everything - to the women and  to the nature , can  stop the degradation of the environment
Keywords: earth democracy; patriarchal approach; domination over the nature; domination over women; Ecofeminism